Review of the Comparative Susceptibility of Microbial Species to Photoinactivation Using 380–480 nm Violet‐Blue Light. (31st March 2018) - Tomb, Rachael M.; White, Tracy A.; Coia, John E.; Anderson, John G.; MacGregor, Scott J.; Maclean, Michelle
Abstract: Antimicrobial violet‐blue light is an emerging technology designed for enhanced clinical decontamination and treatment applications, due to its safety, efficacy and ease of use. This systematized review was designed to compile the current knowledge on the antimicrobial efficacy of 380–480 nm light on a range of health care and food‐related pathogens including vegetative bacteria, bacterial endospores, fungi and viruses. Data were compiled from 79 studies, with the majority focussing on wavelengths in the region of 405 nm. Analysis indicated that Gram‐positive and Gram‐negative vegetative bacteria are the most susceptible organisms, while bacterial endospores, viruses and bacteriophage are the least. Evaluation of the dose required for a 1 log10 reduction of key bacteria compared to population, irradiance and wavelength indicated that microbial titer and light intensity had little effect on the dose of 405 nm light required; however, linear analysis indicated organisms exposed to longer wavelengths of violet‐blue light may require greater doses for inactivation. Additional research is required to ensure this technology can be used effectively, including: investigating inactivation of multidrug‐resistant organisms, fungi, viruses and protozoa; further knowledge about the photodynamic inactivation mechanism of action; the potential for microbial resistance; and the establishment of a standardized exposure methodology. Abstract : A comprehensive systematized review was designed to analyze the antimicrobial efficacy of violet‐blue light between 380 and 480 nm. This review compared the dose requirements for inactivation of a wide range of microorganisms including Gram‐positive and Gram‐negative vegetative bacteria, bacterial endospores, fungal hyphae, fungal conidia, yeasts, bacteriophage and viruses. Data demonstrated vegetative bacteria most susceptible and viruses and bacteriophage least. Additional linear analysis revealed that population density and irradiance are unlikely to effect antibacterial efficacy. However, results also demonstrated that wavelength selected can influence efficacy, with antimicrobial light in the region of 405 nm thought to be more effective for bacterial inactivation than longer wavelengths between 450 and 470 nm.